2018
DOI: 10.1021/acs.energyfuels.7b03378
|View full text |Cite
|
Sign up to set email alerts
|

Torrefaction and Degradative Solvent Extraction As Means of Processing Rice Husk Waste

Abstract: The high moisture level and ash content of biomass often hinder its further processing. In this study, torrefaction and degradative solvent extraction were employed to upgrade rice husk waste. Biomass torrefied at five different temperatures, in addition to dry raw biomass for comparison, was extracted in 1-methylnaphthalene at 300 °C for 1 h. Two solid fractions were obtained: extracted biomass (EB) and residue biomass (RB). The extraction yields of the EB and RB were 12–19.3% and 31.7–52% (db), respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Rice husk (RH) is one of the most abundant agriculture byproducts since rice is the second most cultivated crop and a fifth of its weight is husk. RH contains a high amount of lignin, lignocellulose, and SiO 2 . Therefore, instead of ineffectively using RH as a burning fuel, it is of particular interest to have an efficient process to extract and utilize those useful compounds from RH. Such a process would help in reducing environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk (RH) is one of the most abundant agriculture byproducts since rice is the second most cultivated crop and a fifth of its weight is husk. RH contains a high amount of lignin, lignocellulose, and SiO 2 . Therefore, instead of ineffectively using RH as a burning fuel, it is of particular interest to have an efficient process to extract and utilize those useful compounds from RH. Such a process would help in reducing environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional biochemical and landfilling technologies, thermochemical technologies are more promising for food waste valorization due to higher energy efficiency, higher volume reduction, and faster disposal time. However, food waste needs to be pretreated first to improve some undesired properties such as high moisture content, low homogeneity and bulk density, difficult storage and transport, etc. Recently, torrefaction, usually operating at 200–300 °C under oxidative or inert atmospheres, is considered to be a promising method for food waste pretreatment to enhance the fuel quality. After torrefaction, food waste can be upgraded into a more homogeneous and hydrophobic fuel, with lower O/C ratio, higher energy density, and better grindability. , Therefore, torrefaction not only reduces transportation, storage, and disposal costs, but also produces a better feedstock for the subsequent thermochemical conversion processes (i.e., gasification). , Our previous study has demonstrated that the gasification of torrefied starchy food waste at high temperatures (>900 °C) generates a higher quality syngas compared to that generated from raw starchy food …”
Section: Introductionmentioning
confidence: 99%